Enteroviral pharyngitis diagnosed by reverse transcriptase-polymerase chain reaction. - Sharland, M (1996)
The role of enteroviruses in childhood pharyngitis was investigated using enteroviral specific reverse transcriptase-polymerase chain reaction (RT-PCR). Viral/bacterial throat swabs were taken from 50 children with acute pharyngitis and 26 controls. A positive culture was identified in only 26% of children with pharyngitis (adenovirus 10%, group A streptococci 2%), and none of the controls. Enteroviral RT-PCR was positive in 8% of the pharyngitis group and none of the controls. Enteroviruses are an important cause of pharyngitis in childhood.